Effect of Physical Treatments on Functional Properties of Whey and Soy Protein Isolates in Oleogel Production Through Foam Template Method - Mojtaba Saneei; Sayed Amir Hossein Goli; Hajar Shekarchizadeh; Mehdi Rahimmalek; Antoni Szumny (Molecules)
This study aimed to investigate the impact of physical treatments, namely heat (70 °C for 48 h), atmospheric cold plasma (10 kW for 20 min), and ultrasonic frequency (40 kHz for 15 min), on the physicochemical and interfacial properties of soy protein isolate (SPI) and whey protein isolate (WPI) in the context of oleogel production by foam template (cryogel) method. The physical modification of both SPI and WPI was monitored using SDS-PAGE, Fourier transform infrared spectroscopy (FTIR) spectroscopy, and differential scanning calorimetry (DSC), measuring interfacial tension, color, solubility, foam volume, foam stability, and, finally, the density and oil absorption of the produced cryogel. The findings revealed that the application of ultrasonic waves resulted in a significant reduction in the content of alpha-helical of SPI and WPI while the other treatments increased the content of random coil proteins. FTIR analysis further showed that ultrasonic and heat treatment led to a decrease in C-N tensile vibration within the range of 1200–1650 cm−1 in SPI. Meanwhile, in cold plasma treatment, an increase was observed which was confirmed by the elevation of enthalpy from 100 to 128 kJ/kg. Physical treatments significantly altered the surface properties of both SPI and WPI, where this value was reduced in SPI and increased in WPI. The cold plasma method demonstrated superior performance in enhancing the solubility of SPI from 10 to 58.2%, while the solubility of WPI decreased from 96.4 to 90.4%. By modifying the proteins, the foam volume and oil adsorption ability of the related cryogel improved, as shown by the maximum oil absorption obtained after ultrasonic treatment for SPI (11.6 g/g) and cold plasma (9.17 g/g) for WPI. These results could be useful in applying physical treatments to modify proteins and create the cryogel as an oleogel template for structuring liquid oil and producing innovative health value-added foods.